Una voce parigina nel Futurismo russo: la poesia di Ivan Aksenov - Farsetti, Alessandro (Biblioteca di Studi Slavistici, 2017)
Ivan Aksenov is one of the most neglected figures of early 20th Century Russian literature. The few scholars who have noticed his great originality interpret his verses above all as an application of the principles of Cubist painting in poetry, in the light of the experiences of Mayakovsky &Co.; these investigations denote a poor knowledge of the author, who did not fail to declare the incompatibility between the two artistic media. This book is therefore the first systematic study of Aksenov's poetry, starting from a reflection on the philological state of the texts, to move on to the reconstruction of his aesthetic thought and to integral analyzes of poetic compositions. An unprecedented theory of art emerges from this - which develops ideas of Tolstoy, Vjaceslav Ivanov and Freud - and a production in verses characterized by daring metric innovations and a flow-of-consciousness poetics of the with a subtly humorous urbanism that recalls authors such as Apollinaire and Cendrars. It is thus intended to highlight the peculiarity of Aksenov, the only Russian poet from the Futurist area to have participated, even for a few months, in the cultural life of Paris in the 1910s and an advocate at home of themes and stylistic elements partly related to the French esprit nouveau.